Mechanical properties of aluminum to steel dissimilar spot joints produced by cold metal transfer weld-brazing - Nazmul Huda; James Chen; Adrian P. Gerlich (Forces in Mechanics, 2023)
Spot joints between aluminum and steel sheets were produced by cold metal transfer arc welding using an AlSi3Mn alloy low melting point filler wire. The current study found that by using optimal welding conditions, the thickness of the joint interface was significantly reduced compared to previous studies. The interface thickness increased from a few nanometers at the center of weld to 1.7 micrometers (1.2 mm from center of weld) at periphery of weld. The reduction in joint thickness helped to achieve better joint properties. The tensile shear and fatigue properties of the spot joints were evaluated in conjunction with interrupted mechanical tests to determine the fracture mechanisms. This study investigates the fatigue properties and fracture mechanisms of cold metal transfer arc spot joints, which has not been done previously. The tensile shear fractures exhibit primarily interfacial fracture passing through an intermetallic compound layer at the joint interface. However, three different modes of fractures are observed during fatigue tests, including interfacial fracture, sheet fracture, and mixed-mode fracture. Interrupted fatigue tests reveal numerous crack initiation in pores/particles in the deposited weld metal and coagulation of those cracks leads to sheet fracture during the fatigue tests. Sheet fracture mode fractures are mainly observed during high cycle fatigue conditions.